2008
DOI: 10.1007/s12177-008-9003-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methanolic extract of Allium sativum (AS) in delaying cataract in STZ-induced diabetic rats

Abstract: Glycemic-induced stress is a major culprit contributing to oxidative insult that has far-reaching effects in diabetic cataract worldwide. In an attempt to prevent/delay cataract, many therapeutic agents have been identified, and among these, natural dietary sources have gained pharmacological significance. Hence, we investigated the efficacy of the methanolic garlic extract against diabetic cataract in Wistar rats. Methanolic garlic extract scavenged the transition metal ion-generated H(2)O(2) with an IC(50) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Production of the ONOO À species and its derivatives, whose oxidative capacity is 2000-fold stronger than H 2 O 2 , can lead to a severe oxidative stress reaction, causing extensive damage to lens epithelial cells. 27,28 Over-expression of iNOS had been detected in various eye diseases, 20,[32][33][34][35][36][37] as reported in our previous study. 45 It is widely acknowledged that NF-jB is the major upstream regulator of iNOS.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Production of the ONOO À species and its derivatives, whose oxidative capacity is 2000-fold stronger than H 2 O 2 , can lead to a severe oxidative stress reaction, causing extensive damage to lens epithelial cells. 27,28 Over-expression of iNOS had been detected in various eye diseases, 20,[32][33][34][35][36][37] as reported in our previous study. 45 It is widely acknowledged that NF-jB is the major upstream regulator of iNOS.…”
Section: Discussionmentioning
confidence: 73%
“…30,31 Increased expression of iNOS has been detected in many eye diseases. 20,[32][33][34][35][36][37] Previous research has revealed that both NF-jB and iNOS expression are increased in the LECs of Zucker fatty rats. 38 However, it remains unclear whether NF-jB regulates iNOS expression in human LECs at high glucose levels.…”
mentioning
confidence: 99%
“…Commonly used as a seasoning worldwide, the therapeutic potential of garlic has been reported to include anti-tumor, cardioprotective, anti-diabetic, antimicrobial, amongst others [247]. In addition to delaying onset of streptozotocin-induced cataract in Wistar rats, the methanolic Allium sativum (garlic) extract mitigated hypoglycemia-induced oxidative stress associated with the disease in a dose-dependent manner and restored lenticular SOD and GSH-Px activities and GSH content [248]. In other studies, the flavonoid-rich, aqueous extract of Allium cepa (onion), preserved optical clarity in selenite-treated Wistar Albino rats, in vivo.…”
Section: Plant-derived Compounds and Herbal Remediesmentioning
confidence: 99%
“…Herbal dietary supplementation having diverse antioxidants, fibers, minerals, [164] antiglycant, which show inhibitory activity against α-amylase and α-glucosidase [165] can easily control carbohydrate metabolism in humans. [166] Further, inclusion of white vegetables such as garlic (Allium sativum) provides [167,168] in daily diet provides better diabetic control in T2D patients. [169] Natural components found in garlic oil [170] and its ingredients [171] found more beneficial to control T2D mellitus [172] because they possess antihyperglycemic, antihyperlipidemic, anti-inflammatory, and adenosine deaminase-lowering effects in patients and cut down obesity.…”
Section: Use Of Proper Nutraceuticalsmentioning
confidence: 99%